Dynamics of a Fractional-Order IDSR Rumor Propagation Model with Time Delays - Yahui Niu; Ahmadjan Muhammadhaji (Fractal and Fractional)
With the rapid expansion of the internet and accelerated information dissemination, rumors pose a significant threat to social stability. Effective rumor control requires a thorough understanding of propagation mechanisms. This study develops a Caputo fractional-order IDSR rumor propagation model with time delays. The equilibrium points are identified, and the local asymptotic stability of the system at the positive equilibrium is analyzed. Additionally, the conditions for Hopf bifurcation and its impact on the rumor dynamics are examined. Numerical simulations validate the theoretical findings.